Security Model for Object Oriented Applications - Kaur, Amanpreet (International Journal of Computer Sciences and Engineering, 2025)
Object oriented platform allow us to create ‘n’ number of objects of a class without imposing any constraints. By taking advantage of this feature, unknown objects of known and unknown classes can also be created in an application by the intruder. This paper presents a security model for object oriented platform to overcome such issues. In this paper, I have raised security issues related to object oriented applications. I have also discussed the needs of security for these applications.